Conceptualizing and testing action understanding. (October 2019) - Thompson, Emma L.; Bird, Geoffrey; Catmur, Caroline
Highlights: The term 'action understanding' has previously been defined in three distinct ways. These definitions may map onto distinct psychological processes. Critically examines mirror neuron involvement in each process. Only evidence for mirror neuron involvement in action identification. Abstract: The term 'action understanding' has been defined in several ways since it was first proposed to describe the psychological process subserved by mirror neurons. Here we outline and critique these definitions of 'action understanding' in order to evaluate the claim that mirror neurons perform such a process. We delineate three distinct definitions of 'action understanding', each involving a distinct psychological process. Action identification comprises using the specific configurations of body parts in observed actions to identify those actions, whereas goal identification and intention identification involve generalising across different observed actions to identify the immediate goal of, or the hidden mental state motivating, the actions. This paper discusses the benefits and drawbacks of using these definitions to describe the process purportedly performed by mirror neurons. We then examine each definition in relation to the mirror neuron literature. We conclude that although there is some evidence consistent with the suggestion that mirror neurons contribute to action identification, there is little evidence to support the claim that they contribute to goal or intention identification.